Effect of connection type on galvanic corrosion between lead and copper pipes. Issue 10 (1st October 2013) - Clark, Brandi; Cartier, Clément; Clair, Justin St.; Triantafyllidou, Simoni; Prévost, Michèle; Edwards, Marc
Abstract : Pipe connectors can significantly influence galvanic corrosion between lead and copper pipes by distancing the lead from copper pipe, introducing a third metal, and forming crevices. In this study, the effects of distance, connector material, and crevices on galvanic corrosion were examined, and bench‐scale comparison testing of commercial connectors was conducted using real tap waters. Brass connectors were found to only slightly decrease (< 25%) the galvanic current that sacrifices, or corrodes, lead pipe, with higher reductions for brasses with higher zinc content. Crevices in brass connectors contained water with extremely high levels of lead (up to 9.4 × 10 6 μg/L); in bench‐scale tests, crevices produced approximately four times more lead release to the water than did direct connections.